The use of functional near infrared spectroscopy and gait analysis to characterize cognitive and motor processing in early-stage patients with multiple sclerosis - de Aratanha, Maria Adelia; Balardin, Joana Bisol; Cardoso do Amaral, Carolina; Lacerda, Shirley S.; Sowmy, Tiago Abrão Setrak; Huppert, Theodore J.; Thomaz, Rodrigo Barbosa; Speciali, Danielli S.; Machado, Birajara; Kozasa, Elisa Harumi (Frontiers in Neurology, 2022)
Background: Dual-task paradigms are a known tool to evaluate possible impairments of the motor and cognitive function in patients with multiple sclerosis (MS). A technique to evaluate the cortical function during motion is functional near-infrared spectroscopy (fNIRS). The evaluation of MS course or its treatment with fNIRS associated with gait measurements may be flexible and low-cost, however there is no feasibility study in the literature of these combined techniques in early-stage patients. Objective: To evaluate cortical hemodynamics using fNIRS and gait parameters in patients at early stages of MS and in healthy controls during a dual-task paradigm. Methods: Participants performed cognitive tasks while walking to simulate daily activities. Cortical activation maps and the gait variability were used to evaluate differences between 19 healthy controls and 20 patients with MS. Results and conclusion: The results suggest an enhanced cortical activation in the motor planning areas already at early stages of MS when compared to controls. We also showed that a systematic analysis of the spatiotemporal gait variability parameters indicated differences in the patient population. The association of cortical and gait parameters may reveal possible compensatory mechanisms related to gait during dual tasking at early stages of the disease.